PENGARUH DIAMETER PENSTOCK TERHADAP DEBIT PADA PROTOTIPE PEMBANGKIT LISTRIK TENAGA MIKROHIDRO - Nuraeni, Siti; Adi Nursalim, Agus; Fikri Ulul Albab, Fikri Ulul Albab (Jurnal Fakultas Teknik Kuningan, 2025)
This research aims to compare the diameters of penstocks used in relation to the flow discharge, the influence of penstock diameter on flow discharge, and the efficiency of the generator produced by a microhydro power plant prototipe. The method used is quantitative experimental method by testing the effects of diameters ½', ¾', 1', 1.5', and 2' on the flow discharge of the microhydro power plant prototipe. The results of the research show that the variation in penstock diameter significantly affects the resulting flow discharge. Larger penstock diameter produces higher flow discharge. The penstock diameter contributes 44% to the variation in flow discharge, while 56% is influenced by other factors. The optimal penstock diameter that yields the highest flow discharge is 2', with a discharge of 0.3500 L/s and an average turbine speed of 578.6 RPM. Additionally, the 2' penstock diameter also achieves the most optimal generator efficiency of 20.08% compared to other penstock diameters. This research provides important insights for the development of microhydro power plants to improve their efficiency and performance.